1993
DOI: 10.1111/j.1460-9568.1993.tb00210.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Localization of Interleukin 6 mRNA and Interleukin 6 Receptor mRNA in Rat Brain

Abstract: The distribution of interleukin 6 (IL-6) mRNA and IL-6 receptor (IL-6R) mRNA in the brain of adult male rats was studied at the light microscope level by in situ hybridization histochemistry using 35S-labelled oligonucleotides. The transcripts of both genes were localized in the pyramidal neurons and in the granular neurons of the hippocampus, in neurons of the habenular nucleus as well as in the dorsomedial and ventromedial hypothalamus, in the piriform cortex, in scattered neurons of the cortex and in granul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
151
1
7

Year Published

1996
1996
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(164 citation statements)
references
References 43 publications
5
151
1
7
Order By: Relevance
“…Peripheral IL-6 may cross the blood-brain barrier by an active transport mechanism ) acting in the CNS through specific receptors (Schöbitz et al 1993). Lymphocyte-derived IL-2 has also been suggested to cross the intact blood brain barrier (Waguespack et al 1994) and may gain access to IL-2 receptors on neuronal and glial cells (Araujo et al 1989;Sawada et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral IL-6 may cross the blood-brain barrier by an active transport mechanism ) acting in the CNS through specific receptors (Schöbitz et al 1993). Lymphocyte-derived IL-2 has also been suggested to cross the intact blood brain barrier (Waguespack et al 1994) and may gain access to IL-2 receptors on neuronal and glial cells (Araujo et al 1989;Sawada et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Because IL6 is produced centrally by hypothalamic neurons regulating body composition in rats (Schobitz et al 1993), it has thus been involved in the modulation of body composition. Indeed, IL6 plays a key role in body weight control and is influenced by hormones, TNFα, and the sympathetic nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…First described in 1985, IL-6 is now known to be one of the key cytokines that initiates immune response, especially by activating B cells to synthesize antibodies (Muller et al, 2002b). More recent studies have revealed that this cytokine also arises from both the parenchyma and the fiber tracts (corpus callosum, anterior commissure, fimbria, lateral olfactory tract, optic tract, internal capsule, and corticospinal tracts within the caudate) of the CNS (Schobitz et al, 1993) and can be localized in several neuronal types including pyramidal and granular neurons of the hippocampus, neurons of the habenular nucleus, ventromedial and medial preoptic nuclei of the hypothalamus, cerebellar granular neurons, and pyramidal neurons of the cerebral cortex (Schobitz et al, 1993). Its presence in white matter suggests the expression of IL-6 by oligodendrocytes, the CNS cell type responsible for myelination of axons that comprise the fiber tracts (Yan et al, 1992).…”
Section: Il-6: a Prototype Proinflammatory Cytokine Of The Cnsmentioning
confidence: 99%